Unclogging the Credit Channel: On the Macroeconomics of Banking Frictions - Egle Jakucionyte; Sweder van Wijnbergen (Tinbergen Institute, 2018)
We explore the consequences of different financial frictions on the corporate and banking level for macroeconomic policy responsiveness to major policy measures. We show that both corporate and bank debt overhang greatly reduce the effectiveness of fiscal policy: multipliers turn negative with debt overhang in either sector. The negative impact of banking frictions on macro outcomes increases when a larger part of working capital is financed through credit in addition to investment. Debt overhang in banks leads to positive NPV loans being rejected; after an increase in equity, lending will increase in a debt overhang situation. But after banks increase their equity ratio and subsequently engage less in risk shifting behavior, a decline in lending emerges. Thus the macroeconomic response to higher capital requirements depends on which friction is dominant: when there is debt overhang in banks higher capital leads to more, not less loans and is expansionary; while higher capital requirements lower loan volumes and have a recessionary impact when risk shifting is the problem in banks.We trace the differential importance of corporate versus banking debt overhang back to the different approaches followed on each side of the Atlantic in response to the undercapitalization of the banks after the onset of the financial crisis. We similarly trace macrodevelopment differences in the Southern periphery of Europe and the Northern European countries to differences in the problems and policies in their financial sector.
Keywords: E44; E58; E62; G18; G21; 330; Banking frictions; Fiscal Policy; Capital Requirements; volatility Shocks